THE ULTRASTRUCTURE OF PORPHYRIDIUM CRUENTUM - Gantt, E. (The Rockefeller University Press, 1965)

(untitled)
An electron microscopic examination of Porphyridium cruentum revealed the presence of mitochondria which had been reported absent in this aerobic organism. The chloroplast in this red alga was found to contain small granules (about 320 A) regularly arranged along the parallel chloroplast lamellae. The chloroplast granules differ in size and staining intensity from the ribosomes located in the cytoplasm. Two tubular elements are described. One type (450 to 550 A) is associated with the Golgi bodies. Another type (350 A), in the cell periphery, is believed to connect the endoplasmic reticulum and the cell membrane. Daughter nuclei were found to be positioned at opposite ends of the cell prior to commencement of cell division. Cytokinesis is accomplished by an annular median constriction causing the gradual separation of the chloroplast, pyrenoid, and other cell organelles, resulting in two equal daughter cells. No appreciable differences were observed between cells grown in high light (400 ft-c) and low light (40 ft-c). Structural differences between young and old cells were compared.